Pelatihan Pembuatan Media Pembelajaran Berbantuan Artificial Intelligence (AI) untuk Guru - Yuriananta, Renda; Asteria, Prima Vidya (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
Training on the creation of AI-assisted learning media for teachers was conducted with the aim of improving teachers' skills in utilizing AI technology to create interactive and creative learning media. This initiative was driven by the need for teachers to keep pace with technological advancements in education, particularly in leveraging AI to simplify the process of developing instructional materials. The training took place from July 6–9, 2024, and involved experts from various universities who provided instruction and guidance to participants. Participants were trained to use AI applications such as Gamma AI, InVideo AI, and Suno AI to create presentations, videos, and educational songs. The training results demonstrated that teachers were able to develop AI-based educational media effectively, and a professional network was formed for sharing knowledge and experiences. In conclusion, the training successfully had a positive impact on enhancing teachers' skills and strengthening collaboration among them.